2023
DOI: 10.3390/ma16165717
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Treatment Method Forming New Nano/Micro Hierarchical Structures on Attachment and Proliferation of Osteoblast-like Cells

Jae-Seung Im,
Hyunsuk Choi,
Hyun-Wook An
et al.

Abstract: Titanium (Ti) and Ti-based alloys are commonly used in dental implants, and surface modifications of dental implants are important for achieving osseointegration (i.e., direct connection between the implant surface and bone). This study investigated the effect of an eco-friendly etching solution—a hydrogen peroxide–sodium bicarbonate mixture—on the surface properties and contact angles of osteoblast adhesion and proliferation on Ti surfaces. Disk-shaped Ti specimens were prepared using different surface treatm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Sand-blasted, large-grit, and acid-etched (SLA) technique has emerged as the most commercially successful Ti-based dental implant, which was introduced in 1997. It is a process that involves blasting with coarse abrasive particles followed by acid-etching ( Im et al, 2023 ). SLA generates a topographical surface that exhibits isotropic characteristics.…”
Section: Surface Modification Of Dental Implants and Biomimeticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sand-blasted, large-grit, and acid-etched (SLA) technique has emerged as the most commercially successful Ti-based dental implant, which was introduced in 1997. It is a process that involves blasting with coarse abrasive particles followed by acid-etching ( Im et al, 2023 ). SLA generates a topographical surface that exhibits isotropic characteristics.…”
Section: Surface Modification Of Dental Implants and Biomimeticsmentioning
confidence: 99%
“…This topography consists of macro-scale irregularities, as well as interconnected cavities at the micro-scale and submicro-scale levels ( Kim et al, 2013 ). The greater osseointegration is believed to be attributed to several factors, including improved mechanical interlocking with the adjacent bone, increased surface area, surface energy, protein adsorption, and cell adhesion during the initial stages of wound healing ( Im et al, 2023 ). Instead of the conventional dual etching solutions consisting of sulphuric and hydrochloric acids used in SLA, Jae-Seung Im et al used an eco-friendly hydrogen peroxide (H 2 O 2 )/sodium bicarbonate (NaHCO 3 ) mixture for etching.…”
Section: Surface Modification Of Dental Implants and Biomimeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface roughness can be classified into macroscale, microscale, and nanoscale surface types [ 10 ]. Studies investigating initial fixation and mechanical aspects of implant stability with different surfaces have shown that surfaces with moderate roughness perform better than smooth surfaces [ 11 ]. Implant surfaces with a nanoscale size exhibit superior protein adsorption and enhance osteoblast attachment and proliferation, contributing to early osseointegration [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating initial fixation and mechanical aspects of implant stability with different surfaces have shown that surfaces with moderate roughness perform better than smooth surfaces [ 11 ]. Implant surfaces with a nanoscale size exhibit superior protein adsorption and enhance osteoblast attachment and proliferation, contributing to early osseointegration [ 11 ]. Implant surface roughness ranges from 1 to 23 μm, and measurement methods usually have an accuracy of less than 1 μm [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%